Analisis Vegetasi Beberapa Fragmen Hutan di Kabupaten Timor Tengah Utara - Poleng, Aloisius; Witono, Joko R. (Universitas Atma Jaya Yogyakarta, 2004)
The presentÂ study aims to describe vegetation composition and structure of fragmented areas in Timor Tengah Utara. The study was carried out in three locations : the small forest of Soeb Mountain (L1), the medium forest of Ainiut-Loeram (L2), and the largeÂ forest of Lapeom-Maubesi Mountain (L3). The data were collected using the quadrates method. Each transect is 0,52 ha and thirteen plots (20x20 m) was established. The results show that the number of trees species in the large forest is the highest followed by the medium and the small forests (L3>L2>L1); The tree density in the large forest is the highest, followed by the small and the medium forests (L3>L1>L2). However the highest tree basal area was recorded in the small forest, followed by the large and the medium forests (L1>L3>L2). The species of the highest importance value (IV) at three locations are Pterocarpus indicus Willd., Gossampinus malabarica (DC.) Merr., and Schleichera oleosa (Lour.) Oken.